Miss Meteor - Mejia, Tehlor Kay; McLemore, Anna-Marie (2020)
A teen who secretly arrived with the meteor that gave her small hometown its name discovers that she is turning back into stardust and teams up with her best friend in an effort to secure her human existence by entering a local beauty pageant that has always been won by thin, blonde, white girls
Keywords: Teenage beauty contestants -- Juvenile fiction; Hispanic American teenage girls -- Juvenile fiction; Best friends -- Juvenile fiction; Lesbian teenagers -- Juvenile fiction; Closeted gays -- Juvenile fiction; Young adult fiction; New Mexico -- Juvenile fiction; Fantasy fiction